The rejected body: feminist philosophical reflections on disability - Wendell, Susan (Routledge, 1996)
''Susan Wendell has lived with Chronic Fatigue Syndrome (Myalgic Encephalomyelitis) since 1985. In The Rejected Body, she connects her own experience of illness to feminist theory and the literature of disability. The Rejected Body argues that feminist theorizing has been skewed toward non-disabled experience, and that the knowledge of people with disabilities must be integrated into feminist ethics, discussions of bodily life, and the criticism of the cognitive and social authority of medicine.''
Keywords: 1900-1999; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; capacitisme; corps; cours; discipline; inégalités; phi4336; philosophie; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; systèmes d'oppressions; thématiques; états-unis

Toward a Feminist Theory of Disability - Wendell, Susan (Hypatia, 1989)
We need a feminist theory of disability, both because 16 percent of women are disabled, and because the oppression of disabled people is closely linked to the cultural oppression of the body. Disability is not a biological given; like gender, it is socially constructed from biologically reality. Our culture idealizes the body and demands that we control it. Thus, although most people will be disabled at some time in their lives, the disabled are made "the other," who symbolize failure of control and the threat of pain, limitation, dependency, and death. If disabled people and their knowledge were fully integrated into society, everyone's relation to her/his real body would be liberated.
Keywords: 1900-1999; 1980-1989; EDI; approches et analyses; bioéthique; care; corps; cours; discipline; intersectionnalité; philosophie; premier cycle; périodes historiques; ressource en ligne; santé; sciences humaines; sex1911; sex1920; thématiques; éthique; études critiques du handicap